Intra- and Extra-Articular Deformity of Lower Limb: Tibial Condylar Valgus Osteotomy (TCVO) and Distal Tibial Oblique Osteotomy (DTOO) for Reconstruction of Joint Congruency - Y. Watanabe; N. Takenaka; K. Kinugasa; T. Matsushita; T. Teramoto (Advances in Orthopedics)
Osteotomies are the established surgical procedure for the deformity of the lower limb induced by osteoarthritis (OA) of the knee and ankle. Closed-wedge (CW) and open-wedge (OW) high tibial osteotomy (HTO) are extra-articular surgery, which aim to shift the mechanical axis from medial to slightly lateral and reduce the overload in the medial compartment of the varus deformed knee by extra-articular correction. However, varus deformity of the knee with the teeter effect, which could be accompanied with subluxation and thrust due to the medial-lateral soft tissue imbalance, is not resolved only by the shift of mechanical axis. The depression of the medial tibia plateau, so-called pagoda deformity, is the intra-articular deformity, which could potentially cause the teeter effect and involves intra-articular incongruency. In such case, the osteotomy with novel concept should be developed to overcome the issues, both the imbalance of soft tissue and intra-articular deformity. Tibial condylar valgus osteotomy (TCVO) is an intra-articular osteotomy, which improves the joint congruency of the medial-compartment knee OA with subluxation and/or intra-articular deformity and also provides better joint stability. A similar argument is raised in the treatment of the ankle OA. Low tibial osteotomy (LTO) is an extra-articular surgery to correct malalignment of lower leg. Distal tibial oblique osteotomy (DTOO) is a novel surgery to improve the bony congruency of the ankle OA. In DTOO, the distal tibia is cut obliquely from the proximal medial to the distal lateral in the coronal plane and towards the center of the tibiofibular joint to improve the bony congruency of the ankle joint. Tibial condylar valgus osteotomy (TCVO) and distal tibial oblique osteotomy (DTOO) can correct intra-articular deformity of knee and ankle, respectively. The rationale and indication of TCVO and DTOO for the treatment of the lower limb by reconstructing the joint congruency are discussed.